PROFIL KOMPETENSI PROFESIONAL GURU BK SEKOTA BANDA ACEH - Khajar Ebta Pratama; Martunis Yahya; Qurrata A'yuna (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
The purpose of this research to find out the profile description of guidance and counseling's teacher at Senior High School of Banda Aceh City, the profile of professional competence in guidance and counseling's teacher and efforts to improve their professional competence. This research uses descriptive quantitative approach with survey method. The population in this research was all teachers of guidance and counseling at Senior High School of Banda Aceh City that are 31 teachers. The data collection was done by using questionnaire. The results revealed that: the profile of guidance and counseling's teacher at Senior High School of Banda Aceh City is largely are guidance and counseling graduates. A small portion isn't from guidance and counseling base such as Religious Education, General Education, Education Administration and Psychology. Most of them have passed the certification. Most of teachers have professional competence in middle category. The efforts by teacher of guidance and counseling to improve their professional competence was by mastering the material, structure, concept and mindset of scientific which support tasks as teacher of guidance of counseling/counselor; developing material in providing services of guidance and counseling to students creatively; master the competency standards and basic competence in the field of development; developing professionalism in a sustainable manner by taking reflective action; utilize the technology of information and communication for communicate and self development; add a references of books to expand the knowledge and master the material by taking material from various sources such as the internet, journals, magazines, newspapers and others.Keywords: Profile, Professional Competence, Teacher of Guidance and CounselingABSTRAK Penelitian ini bertujuan untuk mendeskripsikan profil guru BK SMA Negeri Kota Banda Aceh berkaitan dengan kompetensi profesionalnya dan usaha untuk meningkatkan kompetensi. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan metode survei. Populasi dalam penelitian ini adalah seluruh guru BK SMA Negeri se-Kota Banda Aceh yang berjumlah 31 orang. Pengumpulan data dilakukan dengan menggunakan metode angket. Berdasarkan hasil penelitian diketahui bahwa: guru BK SMA Negeri Kota Banda Aceh sebagian besar berasal dari lulusan jurusan/prodi BK. Sebagian kecil dari non BK seperti Pendidikan Agama, Pendidikan Umum, Administrasi Pendidikan dan Psikologi. Sebagian besar mereka telah lulus sertifikasi. Adapun kompetensi profesional mereka sebagian besar berada pada kategori sedang. Usaha yang dilakukan oleh guru BK untuk meningkatkan kompetensi profesionalnya antara lain yaitu berupaya menguasai materi, struktur, konsep dan pola pikir keilmuan yang mendukung tugas sebagai guru BK/konselor; mengembangkan materi dalam pemberian layanan BK kepada siswa secara kreatif; menguasai standar kompetensi dan kompotensi dasar bidang pengembangan yang diampu; mengembangkan keprofesionalan secara berkelanjutan dengan melakukan tindakan reflektif; memanfaatkan teknologi informasi dan komunikasi untuk berkomunikasi dan mengembangkan diri; menambah referensi buku untuk memperluas pengetahuan dan menguasai  materi  dengan  mengambil  bahan  dari berbagai sumber seperti internet, jurnal, majalah, koran dan lain-lain.Kata Kunci: Profil, Kompetensi Profesional, Guru BK